A transferência em um caso clínico - Valli, Cristiane Maretti Marangoni (2007)
The concept of transference within the theory left by Sigmund Freud, is of great importance because it is through its stablishment and interpretation that the analyst has the opportunity to gain access to the unconscious representatives of the analysed individual. The present work aims at investigating and studying the transference that arose during the psychotherapeutical process, according to Freud s lights. The clinical material is the result of a six-month therapy experience, in the environment of a private office. This work relies on the basis of the psychoanalysis as a theory of psychic matters, as well as a method of unconscious investigation and therapeutic technique. The author could gain access to the patient s history and singularity, as the subject of the unconscious, by means of the psychoanalytic method, made possible by the transference